Performance evaluation of the high-speed deep-space optical communication system assisted by preamplified thresholded pulse-position modulation - Gao, Duorui; Li, Tianlun; Xie, Zhuang; He, Yuanchen; Han, Xiaotian; Jia, Shuaiwei; Wang, Wei; Xie, Xiaoping (Frontiers in Physics, 2022)
Deep-space free space optical (FSO) communication utilized the light wave as carriers for information transfer which has the major benefit of small size, light weight, and low consumption compared with the microwave communication loaded with same data rate. M-ary pulse-position-modulation (M-PPM) format is a favourable choice for deep-space FSO communication by means of its high-sensitivity. The preamplified thresholded M-PPM technique has been confirmed and corresponding demonstration has been accomplished with data-rate 1.25 Gbps and 2.00 Gbps separately.The receiving sensitivities (BER@1×10-3) of 1.25 Gbps and 2.00 Gbps 16-PPM have been detected as -57.51 dBm (11.04 photons/bit) and -54.73 dBm (13.13 photons/bit), respectively. Simultaneously, the high extinction ratio M-PPM has been achieved, for example, the extinction ratio of 16-PPM has been detected as 39.51 dB and 38.27 dB for 1.25 Gbps and 2.00 Gbps, respectively, which are 17.60 dB and 17.44 dB higher than that of on-off keying (OOK) modulation, respectively. The results imply our communication scheme possessed high sensitivity, and eliminated the requirements of single photon detector (SPD) and high-speed analog-to-digital converters (ADC), which finds an alternative solution for deep-space FSO communication.